How does obtaining intellectual property rights impact technology commercialization strategy for start-up innovators? Reconciling the effects on licensing vs. financing - Simon Wakeman (European School of Management and Technology (ESMT), 2012)
The importance of intellectual property (IP) rights for commercializing innovation is well established. Moreover, separate streams of literature have shown a positive relationship between IP rights and both product licensing and third-party (especially VC) financing. However, since raising third-party finance enables an innovating firm to continue commercializing its innovation alone, it is not clear how obtaining IP rights will impact the choice between licensing product rights and continuing to commercialize the product alone. This paper attempts to reconcile these two alternative effects of obtaining IP rights and the implications for commercialization strategy. The paper empirically examines the relationship between the status of the primary patent covering an innovation and whether the innovating firm's licenses its innovation or raises external finance. The results show that while filing and allowance of the primary significantly increases the likelihood of raising finance at certain stages of the firm/product's development, and thereby enable the firm to delay licensing, obtaining patent rights has a much larger, positive effect on licensing. While it is not possible to identify the drivers of these different effects from the empirical analysis, the theory suggests that patent filing may act as a signal to financial investors that enable early-stage firms to raise finance, but ultimately they are most valuable as appropriability mechanisms for facilitating financing.
urn:nbn:de:101:1-2013071912546
Keywords: 650; intellectual property; licensing; financing; innovation; strategy; Immaterialgüterrechte; Patent; Innovationsmanagement; Lizenz; Unternehmensfinanzierung; Risikokapital; Theorie